Evaluating the effectiveness of induced seismicity mitigation: Numerical modeling of wastewater injection near Greeley, Colorado. Issue 8 (24th August 2017) - Brown, Megan R. M.; Ge, Shemin; Sheehan, Anne F.; Nakai, Jenny S.
Abstract: Mitigation of injection‐induced seismicity in Greeley, Colorado, is based largely on proximity of wastewater disposal wells to seismicity and consists of cementation of the bottom of wells to eliminate connection between the disposal interval and crystalline basement. Brief injection rate reductions followed felt events, but injection rates returned to high levels, >250, 000 barrels/month, within 6 months. While brief rate reduction reduces seismicity in the short term, overall seismicity is not reduced. We examine contributions to pore pressure change by injection from 22 wells within 30 km of the center of seismicity. The combined injection rate of seven disposal wells within 15 km of the seismicity (Greeley Wells) is correlated with the seismicity rate. We find that injection from NGL‐C4A, the well previously suspected as the likely cause of the induced seismicity, is responsible for 28% of pore pressure increase. The other six Greeley Wells contribute 28% of pore pressure increase, and the 15 Far‐field Wells between 15 and 30 km from the seismicity contribute 44% of pore pressure increase. Modeling results show that NGL‐C4A plays the largest role in increased pore pressure but shows that the six other Greeley Wells have approximately the same influence as NGL‐C4A. Furthermore, the 15 Far‐field Wells have significant influence on pore pressure near the seismicity. Since the main mitigation action of cementing the bottom of wells has not decreased seismicity, mitigation based on reduced injection rates and spacing wells farther apart would likely have a higher potential for success. Key Points: Pore pressure modeling of injection from 22 wastewater disposal wells within 30 km of seismicity Injection from Far‐field Wells between 15 and 30 km contributes a significant portion of pore pressure increase near the induced seismicity Reduction of spatially aggregated injection rate by decrease of individual rates or farther well spacing may be more effective mitigation